(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The results of studies on the assessment of changes in hemodynamic parameters in military personnel with various types of self-regulation of blood circulation are presented. It is demonstrated that in the conditions of high mountains, the cardiovascular type of self-regulation is more optimal for military personnel. A third of the subjects at the stages of long-term activity retained the vascular type and high efficiency, 48% had the vascular type and low efficiency.